Recent Advances in the Synthesis of Hydrogenated Azocine-Containing Molecules - Listratova, Anna V.; Voskressensky, Leonid G. (Synthesis, 2017)
This review covers recent advances in synthesis of azocine-containing systems. The most approaches towards azocines are discussed.1 Introduction2 Ring-Expansion Reaction2.1 Ring-Expansion Reaction of Cyclopentane Containing the 1,4-Diketone Moiety with Primary Amines (from 5 to 8)2.2 Ring-Expansion Reaction of Annulated Tetrahydropyridines under the Action of Activated Alkynes (from 6 to 8)2.3 Reductive Ring-Expansion Reaction of Cyclic Oximes2.4 Other Ring-Expansion Reactions3 Heck Reaction4 Cycloaddition5 Ring-Closing Metathesis (RCM)6 Cyclization6.1 Metal-Catalyzed Cyclization6.2 Radical Cyclization6.3 Friedel–Crafts Cyclization6.4 Other Examples of Cyclizations7 Microwave- and Photo-Assisted Reactions8 Other Methods8.1 Cascade and Tandem Reactions8.2 Aldol Condensation8.3 Thermolysis8.4 Ring Opening8.5 Other Methods9 Conclusion
Keywords: azocine; ring-closing metathesis; cycloaddition; ring expansion; Heck reaction; domino reaction